Pseudomonas aeruginosa biofilms in drinking water and the evolution of antibiotic resistance - Jurgens, Dawn Julie (University of Ottawa (Canada), 2008)
In nature, bacteria grow attached to surfaces in communities called biofilms. Biofilm bacteria are phenotypically distinct from free-floating planktonic bacteria, and one of the phenotypic characteristics of biofilms is that they are highly resistant to antimicrobials. Because of this, biofilms growing inside water distribution systems are not killed by the residual water disinfectant. Bacteria that live inside drinking water distribution system biofilms are under stress due to the constant exposure to the residual disinfectant and the nutritional stress of living in an oligotrophic environment. These stresses can activate the bacterial stress response mechanisms, resulting in increased mutation rates. The mutations that occur are random, but the possibility exists for a mutation to arise that confers increased resistance to antibiotics. The objective of this study was to determine if biofilm bacteria acquire antibiotic resistance when exposed to the residual water disinfectant chloramine. I grew biofilms of Pseudomonas aeruginosa in drinking water bioreactors and treated them with chloramine. The bacteria were sampled over time for isolates that were resistant to ciprofloxacin; isolates were obtained from both the chloramine treated and control biofilms. The ciprofloxacin-resistant isolates had some phenotypic differences from the wildtype P. aeruginosa, as well as being resistant to rifampicin and chloramphenicol, but not resistant to tobramycin and gentamicin.
Keywords: Biology, Microbiology.; Health Sciences, Immunology.